Tubeimoside-1 induces oxidative stress-mediated apoptosis and G0/G1 phase arrest in human prostate carcinoma cells in vitro - Yang Jing-bo; Khan Muhammad; He Yang-yang; Yao Min; Li Yong-ming; Gao Hong-wen; Ma Tong-hui (Acta Pharmacologica Sinica, 2017)
Aim: Tubeimoside-1 (TBMS1), a triterpenoid saponin extracted from the Chinese herbal medicine Bolbostemma paniculatum (Maxim) Franquet (Cucurbitaceae), has shown anticancer activities in various cancer cell lines. The aim of this study was to investigate the anticancer activity and molecular targets of TBMS1 in human prostate cancer cells in vitro. Methods: DU145 and P3 human prostate cancer cells were treated with TBMS1. Cell viability and apoptosis were detected. ROS generation, mitochondrial membrane potential and cell cycle profile were examined. Western blotting was used to measure the expression of relevant proteins in the cells. Results: TBMS1 (5–100 μmol/L) significantly suppressed the viability of DU145 and P3 cells with IC50 values of approximately 10 and 20 μmol/L, respectively. Furthermore, TBMS1 dose-dependently induced apoptosis and cell cycle arrest at G0/G1 phase in DU145 and P3 cells. In DU145 cells, TBMS1 induced mitochondrial apoptosis, evidenced by ROS generation, mitochondrial dysfunction, endoplasmic reticulum stress, modulated Bcl-2 family protein and cleaved caspase-3, and activated ASK-1 and its downstream targets p38 and JNK. The G0/G1 phase arrest was linked to increased expression of p53 and p21 and decreased expression of cyclin E and cdk2. Co-treatment with Z-VAD-FMK (pan-caspase inhibitor) could attenuate TBMS1-induced apoptosis but did not prevent G0/G1 arrest. Moreover, co-treatment with NAC (ROS scavenger), SB203580 (p38 inhibitor), SP600125 (JNK inhibitor) or salubrinal (ER stress inhibitor) significantly attenuated TBMS1-induced apoptosis. Conclusion: TBMS1 induces oxidative stress-mediated apoptosis in DU145 human prostate cancer cells in vitro via the mitochondrial pathway.